Duration of Breastfeeding and Childhood Obesity: A Generalized Propensity Score Approach - Jiang, Miao (Blackwell Science Inc, 2013)
OBJECTIVE: To estimate the effect of breastfeeding duration on childhood obesity. DATA SOURCE: The Child Development Supplement (CDS) of the Panel Study of Income Dynamics (PSID). The PSID provides extensive data on the income and well-being of a representative sample of U.S. families from 1968 to the present. The CDS collects information on the children in PSID families ranging from cognitive, behavioral, and health status to their family and neighborhood environment. The first two waves of the CDS were conducted in 1997 and 2002, respectively. The data provide information on 3,271 children and their mothers. STUDY DESIGN: We use the generalized propensity score to adjust for confounding based on continuous treatment, and the general additive model to analyze the adjusted association between treatment and the outcome conditional on the propensity score. The main outcome is the body mass index (BMI) directly assessed during the in-person interview in 2002. Covariates include family, maternal, and child characteristics, many of which were measured in the year the child was born. PRINCIPAL FINDINGS: After using propensity scores to adjust for confounding, the relationship between breastfeeding duration and childhood BMI is trivially small across a range of model specifications, and none of them is statistically significant except the unadjusted model. CONCLUSIONS: The causal link between duration of breastfeeding and childhood obesity has not been established. Any recommendation of promoting breastfeeding to reduce childhood obesity is premature.